Digital signal processing with field programmable gate arrays - Meyer-Baese, U., ....- (Berlin : Springer, 2001)
Contents: --------- 1. Introduction 2. Computer arithmetic 3. Finite impulse response (FIR) digital filters 4. Infinite impulse response (IIR) digital filters 5. Multirate signal processing 6. Fourier transforms 7. Advanced topics
Keywords: Digitale filters; Field programmable gate arrays; Signaaltheorie; Signal processing -- Digital techniques